2021
DOI: 10.1108/jrim-05-2020-0104
|View full text |Cite
|
Sign up to set email alerts
|

Customer engagement and value co-creation/destruction: the internal fostering and hindering factors and actors in the tourist/hotel experience

Abstract: PurposeThe customer as an active and engaged value co-creator raises new challenges for theory and practice, especially in the hospitality industry. However, the connection between engagement and co-creation is little studied in the hotel/tourism literature. This paper proposes a connection between customer engagement (CE) and value co-creation frameworks to ascertain and depict the internal actors' activities and factors that foster or hinder guests' co-creation and destruction of value.Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 44 publications
1
27
0
2
Order By: Relevance
“…The findings demonstrated that participants had higher trust, satisfaction, and commitment in a high degree of co-creation conditions than in a low degree of co-creation conditions. Positive interaction and engagement encourage customers to deploy more resources in order to create value for themselves (Nangpiire, Silva, & Alves, 2021). The high degree of co-creation promotes more interaction and engagement, thus it increases satisfaction, trust, and commitment.…”
Section: Discussionmentioning
confidence: 99%
“…The findings demonstrated that participants had higher trust, satisfaction, and commitment in a high degree of co-creation conditions than in a low degree of co-creation conditions. Positive interaction and engagement encourage customers to deploy more resources in order to create value for themselves (Nangpiire, Silva, & Alves, 2021). The high degree of co-creation promotes more interaction and engagement, thus it increases satisfaction, trust, and commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when they exchange useful information and give brand advice to other community members, they tend to report higher levels of satisfaction (Niedermeier et al, 2019). For example, Nangpiire et al (2021) found that positive engagement fosters customer interactions, which lead to value co-creation. Further, customer-to-customer interactions can influence customer satisfaction with the service platform since such interactions can clarify expectations and reduce role ambiguity through customer participation (Luo et al, 2019).…”
Section: Customer Brand Engagementmentioning
confidence: 99%
“…Evidence indicates that customers and service providers are open to interacting and sharing resources (in the form of time, energy and information) to provide more personalised service experiences (Kandampully et al. , 2018; Nangpiire et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they focus on distinguishing themselves from competitors to target end consumers effectively (Mazzarolo et al, 2021). Evidence indicates that customers and service providers are open to interacting and sharing resources (in the form of time, energy and information) to provide more personalised service experiences (Kandampully et al, 2018;Nangpiire et al, 2021).…”
Section: Introductionmentioning
confidence: 99%